KNOWLEDGE OF ENGLISH AS AN ASSET OF HUMAN CAPITAL - Olena Grishnova; Serhii Panaseiko (Izdevnieciba "Baltija Publishing", 2021)
The article is devoted to the study of the relationship between the knowledge of English (as a foreign language) and the level of wages. The purpose of this paper is to confirm or refute the claim that there is a correlation between these two categories. Value/originality. The authors proved that English proficiency has the potential to increase workers' earnings. Factors such as work experience and organizational size were included in the study. Moreover, the paper suggests that learning English develops qualities valued by employers and increases employee competitiveness. The empirical base is the reports of EF (Education First), Cambridge English and QS. In particular, EF provides its annual reports summarizing the relationship between English and the various categories. The Cambridge English and QS report showed the percentage of employers who offer the best packages to applicants with good English skills. In Ukraine this figure is 83%. This study proved the existence of a correlation between the knowledge of English and the level of wages. The expected salary growth of a potential employee may well range from 8.5% to 34.1%, which was studied on the example of vacancies for marketers. Such wage differences exist not only because of the need to incorporate linguistic knowledge into the job, but also because of the skills that can be acquired through training. Good memory, better cognitive skills, the ability to stay focused and organized while performing tasks - these are the qualities that define a person who is most likely to handle all his/her responsibilities properly. In addition, it is determined that B2 (Upper-intermediate) is the most sought-after level of English among Kyiv marketers. One of the conclusions of the study is that people with no work experience but with linguistic skills have a chance to get a job, although the percentage of such vacancies is small.